PERKAWINAN WANITA USIA DINI PADA KELUARGA MISKIN DI PROVINSI SUMATERA SELATAN - Evy Ratna Kartika Waty; Vegitya Ramadhani Putri (Sosio Konsepsia, 2009)
Child marriage mostly happens in rural societies with many circumstances. Education's less-access, poverty, isolated-area, jobless are many factors that influencing child-marriages. From socio-economic aspect, these kinds of marriages causing school-drop-out, less life-skill, less knowledge, less self-confidence,Â and less job participation. That problem is most consequential to women that involve on child-marriages.Â Those condition impact to family's poverty and economic-dependency. Women with child-marriage also have suffered with negative on their reproduction health. Most of child-marriage happens btj manipulation of ages and time of their birth, which is as important condition to be a legal marriage. This research found that this child-marriage is psychological and physical violence. Women as teenagers whom in child-marriages are forced to involve in adult life in most of them had emotional depression and faced many socialeconomy difficulties.